The effects of acupuncture on patients with premature ovarian insufficiency and polycystic ovary syndrome: an umbrella review of systematic reviews and meta-analyses - Bai, Tianyu; Deng, Xinyun; Bi, Jieyu; Ni, Linlin; Li, Zhaohui; Zhuo, Xiumei (Frontiers in Medicine, 2024)
Background: Previous studies have suggested that acupuncture could improve the clinical outcomes of women with premature ovarian insufficiency failure (POFPOI) and polycystic ovary syndrome (PCOS). However recent meta-analyses have provided inconclusive findings. This umbrella meta-analysies aimed to explore the effect of acupuncture therapies on PCOS and POIPOF outcomes.Methods: A systematic literature search was carried out in in PubMed, Scopus, Web of Knowledge, and Chinese databases, including Wan Fang Data Knowledge Service Platform, CBM, CNKI, and VIP multiple databases up until April 2024 to gather relevant studies.Inclusion criteria were meta-analyses on the effect of acupuncture or combined therapies with standard medications or traditional Chinese medicine (TCM) on PCOS and POIPOF., 2) Tthe outcomes were pregnancy rates, ovulation rates, hormone levels, glycemic indices, resumption of menstruation, endometrial thickness, live birth rates, abortion rates, and body mass index (BMI). Studies with irrelevant interventions, animal studies, reviews without quantitative analysis, and studies with insufficient data were excluded. Standardized mean difference (SMD) with a 95% confidence interval (CI) and relative risk (RR) with a 95% CI were used as effect sizes for to pooling the data utilizing using a random effects model. for continuous and binomial outcomes, respectively.Results: A total of 38 meta-analyses, 20 studies (sample size: 27,106 patients) for PCOS and 18 studies (sample size: 19,098 patients) for POIPOF, were included. Overall, in women with PCOS, acupuncture therapies were significantly associated with a higher total effective rate, pregnancy rate, ovulation rate, and reduced serum levels of luteinizing hormone (LH), testosterone, LH/follicle-stimulating hormone (FSH), insulin resistance, and body mass indexBMI. Moreover, FSH levels, fasting glucose, and fasting insulin levels were improved in subgroup analyses. For POIPOF, acupuncture significantly improved effective rate, and serum levels of LH, FSH, LH/FSH ratio, and estradiol.Acupuncture-related therapies improve total effective rate, pregnancy rate, and metabolic and hormonal imbalances in patients with POIPOF and PCOS.